Hubungan Tingkat Kecemasan Terhadap Siklus Menstruasi Pada Mahasiswi Tingkat Akhir Di Stikes Bani Saleh - H. Wada, Fauziah; April Rianti, Ananda; Imbang Satriawan Hasiolan, Mara; Prima, Ashar; Mortin Andas, Amzal; Puspitasari, Indah (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Menstruation is the process of detachment of the uterine wall followed by bleeding that occurs repeatedly every month and eventually forms a menstrual cycle. An irregular menstrual cycle is one of the disorders and can be caused by anxiety. The purpose of this study is to determine the relationship between the level of anxiety towards final year female students at STIKes Bani Saleh. Design this research is quantitatively descriptive with a cross sectional approach. The population of this study was 124 respondents using the purposive sampling method. The data analysis technique of this study uses a spearman rank test. The results showed that 34% of respondents experienced no anxiety, 33% mild anxiety levels, 13% moderate anxiety levels, 13% severe anxiety levels, 7% severe anxiety levels once respondents had a normal menstrual cycle of 21-35 days. The results of  the spearman rank  test showed a significant value of p = 0.258. The conclusion of this study showed that there was no relationship between the level of anxiety towards the menstrual cycle in final year female students at STIKes Bani Saleh. It is hoped that respondents will better understand that mental health plays an important role in the menstrual cycle. Therefore, maintaining emotional balance is very necessary to keep the menstrual cycle regular.